Património geomorfológico no Litoral Sudoeste de Portugal - Pereira, Ana Ramos (Finisterra, 1995)
GEOMORPHOLOGICAL PATRIMONY ON PORTUGUESE SOUTHWEST COAST - Within the scope of environmental concerns that challenge mankind, namely the management of biodiversity and the preservation and conservation of landscapes, the aim of this paper is to define the geomorphological patrimony and the establishment of geomorphological ways. Landscapes are here regarded as the spatial expression of the interaction between biophysical and socio-economical componets that form the environmental system. In the case of the Portuguese Southwest, the geomorphological component of the environmental system is assumed to be structuring element of the present landscape. In this sense, geomorphological patrimony is taken as a set of landforms (soils and correlative deposits) with clear scientific interest by their genetic and degree of preservation characteristics, by their rarity and/or originality, by their degree of vulnerability or moreover by the way they are connected in terms of space. Such landforms deserve to be preserved.The Portuguese Southwest includes a protected by law area (Protected landscape area of Southwest of Alentejo and Costa Vicentina, set by the Decree-law nº241/88 June 7). It keeps a quite diversified and rich geomorphological patrimony, generally well preserved, in a mainly rural area (fig.1). Its geomorphological evolution is the result of the continental and sea planation, as well as tectonic events, and it is a good example of the coastal landscapes evolution (figs.2,3,4). We therefore propose the creation of spacial protection ways, geomorphological ways (with geomorphological sites with particular interest), on the strength of their scientific interest, and also because they are the record of the landscape evolution and their environmental conditions (fig.5).